Hungarian Monitoring, 11 November 1988 . [Magyar rádiófigyelő], 1988. november 11 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Preparations for next year's CPSU Central Committee session discussion nationalities questions - Background to the Jenninger scandal - Oppositionists arrested in Prague - Formation of independent Palestinian state expected - Polish United Workers' Party in crisis Domestic Affairs: - János Kádár receives A. Jakovlev, secretary of the CPSU Central Committee - Justice minister Kálmán Kulcsár on new draft law on right to associate and assemble - Rezső Nyers on the chances of forming a multi-party system - Peace activists from 30 countries arrive in Budapest for a three-day peace meeting - Socialist countries' sports ministers in Budapest discuss and accept appeal regarding doping scandal Külpolitika: - Előkészületek az SZKP KB nemzetiségi kérdésekkel foglalkozó jövő évi ülésére - A Jenninger-botrány hátteréről - Ellenzékieket tartóztattak le Prágában - Önálló palesztin állam kikiáltása várható - Válságban a LEMP Belpolitika: - KÁDÁR János fogadta A. Jakovlevet az SZKP KB titkárát - Kulcsár Kálmán igazságügy miniszter az egyesülési és gyülekezési jog új törvénytervezetéről - Nyers Rezső a többpárti rendszer kialakulásának esélyeiről - 30 országból érkeztek békeaktivisták a Budapesten megnyílt 3 napos béketalálkozóra - A dopping ügyről tárgyaltak és felhívást fogadtak el a szocialista országok sportminiszterei Budapesten